Predictors of surgical complications in boys with hypospadias: Data from an internationa registry - GÜRAN, TÜLAY (My University, 2023)
Background Complications are frequently reported after hypospadias repair and there is a need to understand the factors that influence their occurrence. Methods Data from boys with hypospadias born between 2000 and 2020 were obtained from the International Disorders of Sex Development (I-DSD) Registry. Logistic regressions, fisher\"s exact tests and spearman\"s correlation tests were performed on the data to assess associations between clinical factors and complication rates. Results Of the 551 eligible boys, data were available on 160 (29%). Within the cohort, the median (range) External Masculinization Score (EMS) was 6 (2, 9). All presented with one or more additional genital malformation and 61 (38%) presented with additional extragenital malformations. Disorders of androgen action, androgen synthesis and gonadal development were diagnosed in 28 (18%), 22 (14%) and 9 (6%) boys, respectively. The remaining 101 (62%) patients were diagnosed as having non-specific 46,XY Disorders of Sex Development. Eighty (50%) boys had evidence of abnormal biochemistry, and gene variants were identified in 42 (26%). Median age at first hypospadias surgery was 2 years (0, 9), and median length of follow-up was 5 years (0, 17). Postsurgical complications were noted in 102 (64%) boys. There were no significant associations with postsurgical complications. Conclusions Boys with proximal hypospadias in the I-DSD Registry have high rates of additional comorbidities and a high risk of postoperative complications. No clinical factors were significantly associated with complication rates. High complication rates with no observable cause suggest the involvement of other factors which need investigation.
Keywords: Tıp; Dahili Tıp Bilimleri; Çocuk Sağlığı ve Hastalıkları; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Child Health and Diseases; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; PEDİATRİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; PEDIATRICS; Cerrahi; Pediatri, Perinatoloji ve Çocuk Sağlığı; Surgery; Pediatrics, Perinatology and Child Health; Endocrinology; Pediatrics